(untitled) (Research, Society and Development, 2022)
To make production systems more competitive and ensure production sustainability, it is necessary to adopt techniques with less environmental impact, which bring diversification and improve yields per area. The objective of this work was to analyze the synergistic effect between the cultivation of corn for silage in succession to the crop residues of different species of cover crops and the inoculation of seeds with Azospirillum brasilense in sandy soil, located in the municipality of Nova Andradina-MS. The experimental design used was the DBC for cover crops, and a DBC in an 8x2 factorial scheme for maize, with 8 combinations of cover crops species, single or intercropped, and two levels for the inoculation factor with A. brasiliense, with inoculation via corn seed and the control without inoculation with the growth promoting bacteria. In cover crops the dry biomass yield was evaluated, and in corn the variables biomass and grain yield, plant height, ear length, stem diameters, ear diameters, in addition to the percentage of the morphological components of the crop’s in stems, leaves, panicles, bracts and cobs. The single or intercropped cultivation of some species of cover crops in succession to maize for silage promoted an increase in the agronomic components of. A. brasilense maize, negatively influencing the height of maize plants in the 2020/2021 harvest.